2018
DOI: 10.1101/334839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interplay between coding and exonic splicing regulatory sequences

Abstract: 20The inclusion of exons during the splicing process depends on the binding of splicing factors to short 21 low-complexity regulatory sequences. The relationship between exonic splicing regulatory sequences 22 and coding sequences is still poorly understood. We demonstrate that exons that are coregulated by 23 any splicing factor share a similar nucleotide composition bias. We next demonstrate that 24 coregulated exons preferentially code for amino acids with similar physicochemical properties 25 because of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been reported that RBPs, such as Embryonic lethal abnormal vision like protein family (ELVAL), TAR DNA-binding protein 43 (TDP43), eukaryotic initiation factor 2 (eIF2α)W2, play pivotal regulatory roles in the development of neurodegenerative diseases including AD [8][9][10] . TRA2A is located at 7p15.3 and plays an important role in the splicing regulatory process of pre-mRNA [11] . TRA2A is highly expressed in the neurodegenerative disease, fragile Xassociated tremor/ataxia syndrome (FXTAS).…”
Section: Abstract Blood Brain Barrier Alzheimer's Disease Tra2a LImentioning
confidence: 99%
“…It has been reported that RBPs, such as Embryonic lethal abnormal vision like protein family (ELVAL), TAR DNA-binding protein 43 (TDP43), eukaryotic initiation factor 2 (eIF2α)W2, play pivotal regulatory roles in the development of neurodegenerative diseases including AD [8][9][10] . TRA2A is located at 7p15.3 and plays an important role in the splicing regulatory process of pre-mRNA [11] . TRA2A is highly expressed in the neurodegenerative disease, fragile Xassociated tremor/ataxia syndrome (FXTAS).…”
Section: Abstract Blood Brain Barrier Alzheimer's Disease Tra2a LImentioning
confidence: 99%